Application of emergency peritioneal dialysis in chronic renocardiac syndrome complicated with refractory congestive heart failure - HUANG Jin-ping; HUA Du-juan; CHEN Hua-lan (Linchuang shenzangbing zazhi)
Objective To investigate the effectiveness and safety of emergency peritoneal dialysis in the treatment of chronic renocardiac syndrome（CRCS） patients complicated with refractory congestive heart failure（RCHF）.Methods Patients with chronic kidney disease,whose estimated glomerular filtration rate（eGFR） was less than 30 ml· min-1 ·（1.73 m2）-1 and symptoms of heart failure（heart function Ⅲ-Ⅳ level,based on New York Heart Disease Association） could not be improved or worsened after regular anti-heart failure treatment（the treatment of rational diuretic,blood vessel expansion agent and digoxin）,were diagnosed as CRCS complicated with RCHF.Twelve patients with such disease were enrolled in Suizhou Central Hospital from July 2014 to August 2015.On the basis of anti-heart failure treatment,emergency peritoneal dialysis treatment was performed.The changes of clinical symptoms,cardiac function and renal function were compared before and after the treatment,and the complications of emergency peritoneal dialysis were observed as well.Results（1） Heart failure symptoms of all patients were relieved after treatment for 7 days.（2）The mean arterial pressure,heart rate,type B brain natriuretic peptide,serum creatinine,blood urea nitrogen,and serum potassium were decreased significantly after treatment（P<0.05）;（3）The left ventricular ejection fraction and carbon dioxide binding rate were significantly increased after treatment（P<0.05）;（4）In this study,there was 1 case of peritoneal dialysate leakage amd 3 cases of inadequate drainage,and there were no cases of peritonitis,bleeding,organ damage,incubating place infection and other serious complications.Conclusions The emergency peritoneal dialysis based on conventional anti-heart failure treatment can significantly improve the heart and kidney function in patients with CRCS complicated with RCHF,and it is simple operation,has less adverse reactions,and is worth clinical promotion and applicatioa In the absence of hemodialysis or CRRT,we can first use emergency peritoneal dialysis treating patients with CRCS complicated with RCHF.